Folk Onomastics Study of Anthroponymy Found in Babad Banjoemas Wirjaatmadjan - Chusni Hadiati (Universitas Sanata Dharma, 2021)
Folk onomastics is a sub-category of socio-onomastics which deals with people’s beliefs and perceptions of names and name use. Interestingly, pragmatics also plays important role in the study of onomastics as names cannot be split up from the context where they are used. The phenomenon of anthroponymy that gradually advances relates to the development of human civilization. Personal name is very pivotal in human life due to the role of name bearers’ in history. Name is not only a name for it carries something along with it throughout the time particularly those who have power and position in history. Babad Banjoemas Wirjaatmadjan (BBW) was a chronicle of Banyumas regency from 1582 until 1932 which was written by Raden Wirjaatmadjan and continued by Raden Poerwasoepradja. As a chronicle of Banyumas regency, BBW displays historical names and aliases related to the cultural context of Banyumas. This article tries to dig out the phenomenon of anthroponymy of Banyumas’ regency leaders (bupati) in BBW as the names indicate the historical background of the bearers. Thus, the research spotlights the cultural values carried by alias or pseudonym of Banyumas leaders. Utilizing descriptive qualitative and library research, I found out that bupati’s names and aliases in BBW were classified based on five conditions: place of death, place of retirement, place of banishment, medal of appreciation, and lifelong action. The result highlights the traditional proverb that good men must die but death cannot kill their names.